2014
DOI: 10.1111/bcp.12444
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic study of gentamicin in a large cohort of premature and term neonates

Abstract: AIMThis study aims to investigate the clinical and demographic factors influencing gentamicin pharmacokinetics in a large cohort of unselected premature and term newborns and to evaluate optimal regimens in this population. METHODSAll gentamicin concentration data, along with clinical and demographic characteristics, were retrieved from medical charts in a Neonatal Intensive Care Unit over 5 years within the frame of a routine therapeutic drug monitoring programme. Data were described using non-linear mixed-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
83
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 69 publications
6
83
1
Order By: Relevance
“…The values of the PK parameters for a typical infant from the model-building data set (weight, 2.12 kg; PMA, 33.0 weeks; PNA, 5.4 days; MSCr, 78 mol/liter; TSCr, 71.4 mol/liter) were 0.077 liters/h and 0.80 liters (and 0.10 liters/h and 0.78 liters for a neonate from the evaluation data set) for CL and V, respectively. These values are in agreement with clearance estimates from previous neonatal studies of gentamicin pharmacokinetics (13,14,18,(22)(23)(24). The reported value (0.026 liters/h) for CL from Nielsen et al (21) may appear to be lower, but using our median demographic values in their model, the CL value becomes similar to our estimates (0.095 liters/h).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The values of the PK parameters for a typical infant from the model-building data set (weight, 2.12 kg; PMA, 33.0 weeks; PNA, 5.4 days; MSCr, 78 mol/liter; TSCr, 71.4 mol/liter) were 0.077 liters/h and 0.80 liters (and 0.10 liters/h and 0.78 liters for a neonate from the evaluation data set) for CL and V, respectively. These values are in agreement with clearance estimates from previous neonatal studies of gentamicin pharmacokinetics (13,14,18,(22)(23)(24). The reported value (0.026 liters/h) for CL from Nielsen et al (21) may appear to be lower, but using our median demographic values in their model, the CL value becomes similar to our estimates (0.095 liters/h).…”
Section: Discussionsupporting
confidence: 91%
“…3). However, due to unavailability of some covariates in our data set, three models were used without all of the covariates (Apgar score [15,19], sepsis [19], and comedication with dopamine [23]) included, which could explain their worse predictive performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, a new PK model of gentamicin in neonates was developed, as previously reported PK models of gentamicin in neonates (9,11,12) did not describe our data well. The results for bias (MPE) and precision (RMSE) of these candidate models showed that all concentrations (peak, trough, and other concentrations) and peak concentrations alone of our patient population were overpredicted.…”
Section: Discussionmentioning
confidence: 96%
“…In the study of De Cock et al (12), the percentage of patients with ibuprofen as comedication was much higher than in our population (43% versus 8%). Fuchs et al (11) incorporated dopamine comedication as a covariate on Cl in their PK model. We did not, however, retrieve data on dopamine use in our cohort of neonates, as there is conflicting literature on the effect of dopamine on the glomerular filtration rate and Cl of aminoglycosides in neonates (13)(14)(15)(16)(17), and at the time of study design, the PK model of Fuchs et al (11) was not yet published.…”
Section: Discussionmentioning
confidence: 99%